2020
DOI: 10.3390/rs12162545
|View full text |Cite
|
Sign up to set email alerts
|

Vegetated Target Decorrelation in SAR and Interferometry: Models, Simulation, and Performance Evaluation

Abstract: The paper addresses the temporal stability of distributed targets, particularly referring to vegetation, to evaluate the degradation affecting synthetic aperture radar (SAR) imaging and repeat-pass interferometry, and provide efficient SAR simulation schemes for generating big dataset from wide areas. The models that are mostly adopted in literature are critically reviewed, and aim to study decorrelation in a range of time (from hours to days), of interest for long-term SAR, such as ground-based or geosynchron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 35 publications
(109 reference statements)
0
11
0
Order By: Relevance
“…Step 1: according to the relevant influencing factors in the development process of e-government, select the appropriate indicator data of e-government performance evaluation, use relevant algorithms to conduct standardized processing of indicator data [28], and then process the processed indicator data X 1 , X 2 , X 3 , ..., X n as the input value is of the PSO-BP neural network at the input level.…”
Section: Online Teaching Quality Evaluation Model Based On Hierarchical Pso-bp Neural Networkmentioning
confidence: 99%
See 1 more Smart Citation
“…Step 1: according to the relevant influencing factors in the development process of e-government, select the appropriate indicator data of e-government performance evaluation, use relevant algorithms to conduct standardized processing of indicator data [28], and then process the processed indicator data X 1 , X 2 , X 3 , ..., X n as the input value is of the PSO-BP neural network at the input level.…”
Section: Online Teaching Quality Evaluation Model Based On Hierarchical Pso-bp Neural Networkmentioning
confidence: 99%
“…Multiobjective Evolution of Fuzzy Rough Neural Network has been researched [26,27]. A minimum center distance rule activation method and Target Decorrelation in SAR are discussed [28,29].…”
Section: Introductionmentioning
confidence: 99%
“…With the recent availability of S1B data, the experiment conducted in [12] can be extended by reducing the temporal baseline to six days, which would reduce the temporal decorrelation between the images [4,18]. This should lead to higher coherence values for post-mowing short vegetation conditions, thus enhancing the signatures of the farming events in the coherence time series.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, authors of [3] showed that the short-term variable reflectivity induced by wind, typical of vegetated scenarios, can be theoretically characterized and modeled. In [4] different theoretical models for the temporal decorrelation of GBSAR images in vegetated scenarios are examined. For the short-term signal variability, a model with dependence on the wind speed is presented and validated for experimental data acquired in different scenarios.…”
Section: Introductionmentioning
confidence: 99%